1994
DOI: 10.1192/bjp.165.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Versus Hospital-Based Care for People with Serious Mental Illness

Abstract: It is unclear how much the gain until 20 months from home-based care was due to its site of care, its being problem-centred, its teaching of daily living skills, its assertive follow-up, the home care team's keeping responsibility for any in-patient phase, its coordination of total care (case management), or to other care components. Home-based care is hard to organise and vulnerable to many factors, and needs careful training and clinical audit if gains are to be sustained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0
15

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(121 citation statements)
references
References 37 publications
3
103
0
15
Order By: Relevance
“…Reduction in social isolation and better recreational and improved personal care are the most consistent findings (Stein & Test, 1980;Hoult et al, 1983;Goering et al, 1988;McFarlane et al, 1992;Marks et al, 1994;McGrew et al, 1995).…”
Section: Improvements In Symptoms and Functionmentioning
confidence: 85%
See 2 more Smart Citations
“…Reduction in social isolation and better recreational and improved personal care are the most consistent findings (Stein & Test, 1980;Hoult et al, 1983;Goering et al, 1988;McFarlane et al, 1992;Marks et al, 1994;McGrew et al, 1995).…”
Section: Improvements In Symptoms and Functionmentioning
confidence: 85%
“…In most studies, patients and their relatives expressed a greater satisfaction with case manage ment services than with standard care (Stein & Test, 1980;Marks et al, 1994). No study has found standard hospital care to be superior to ACT on any of these outcome measures.…”
Section: Greater Patient Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les résultats des études effectuées permettent de constater que les familles sont généralement moins satisfaites des services de santé mentale que leurs proches (Rugerri et al, 1994) et que le degré de satisfaction des familles est moins élevé pour ce qui est des services offerts à l'hôpital, que pour ceux offerts dans la communauté (Solomon et Marcenko, 1992 ;Marks et al, 1994 ;Audini et al, 1994). Selon certains auteurs (Grella et Gruski, 1989 ;Solomon et Marcenko, 1992 ;Hanson, 1995 ;Leavy et al, 1997), les contacts qu'ont les familles avec les intervenants seraient un des points majeurs d'insatisfaction.…”
Section: Remerciementsunclassified
“…The reality is not so clear-cut, Joy et al (1998) report only five methodologically adequate controlled studies. Of these, only one, the Daily Living Programme (Marks et al, 1994), was carried out in the UK. The other four studies were undertaken 20 or more years ago in Canada, Australia and the USA (a country where only 15% of a sample of psychiatrists made a home visit in the past year (Reding et al, 1994)).…”
mentioning
confidence: 99%